Getting to the heart of stem cell research: an interview with Christine Mummery - Christine Mummery (The Company of Biologists, 2023)
Professor Christine Mummery has pioneered the use of pluripotent stem cell models to investigate heart development and disease, and pushed the boundaries of what can be achieved with these versatile cells. In 2008, she became Chair of Developmental Biology at Leiden University Medical Centre, where she has refined and advanced in vitro models of the heart and now harnesses their clinical potential to screen drugs and personalise treatments for patients with various types of heart disease. Christine has become integral to the stem cell community by promoting cross-disciplinary research and serving on several Ethical Councils, Scientific Advisory Boards and Editorial Boards. Her influence in the field of stem cell research led her to become the president of International Society for Stem Cell Research in 2020, and she has won numerous awards, including the Hans Bloemendal Medal 2014 for innovative interdisciplinary research, with Gordon Keller, the prestigious Lefoulon-Delalande Prize 2021 and the International Society for Stem Cell Research (ISSCR) Public Service Award 2023. In this interview, Christine shares her career trajectory, how disease modelling is shifting towards advanced in vitro systems and what challenges the field has yet to overcome.